Case management as a high-risk prenatal care strategy - Leticia Gramazio Soares; Ieda Harumi Higarashi
ABSTRACT Objective: to discuss the benefits of using high-risk prenatal case management. Method: a qualitative, convergent care study with six high-risk pregnant women, performed in a municipality in the south of Brazil. Data were produced by case management from April to August of 2017 through observation-participant. Analysis followed the processes of Convergent Care Research: apprehension, synthesis, theorization and transfer. Results: case management identified important elements in the care of pregnant women, which denoted a greater complexity to the cases; was shown as a relevant space for nurses to act, because it is an intervention that requires knowledge and specific skills. Final considerations: case management provides differentiated management in complex cases, facilitates the flow between health services, concretizing the comprehensiveness and equity of the care. It was found, in the convergence between research and care, that participants were benefited by case management.